Предмет: Алгебра,
автор: poxertyk
Разложи на множители: p³−p²b−pb²+b³
Ответы
Автор ответа:
0
Ответ:
Объяснение:
..,.....,...
Приложения:
Автор ответа:
1
Ответ:
(p - b)²(p + b)
Объяснение:
p³ − p²b − pb² + b³ = p²(p - b) - b²(p -b) = (p² - b²)(p - b) = (p - b)(p + b)(p - b) = (p - b)²(p + b)
Похожие вопросы
Предмет: Немецкий язык,
автор: ilka1998
Предмет: Русский язык,
автор: задача37
Предмет: Другие предметы,
автор: Аноним
Предмет: Русский язык,
автор: TheAgentSquid
Предмет: История,
автор: vladvoroxov